How Well Do Neurologic Symptoms Identify Individuals With Neurosyphilis?. (9th September 2017) - Davis, Arielle P; Stern, Joshua; Tantalo, Lauren; Sahi, Sharon; Holte, Sarah; Dunaway, Shelia; Marra, Christina M
Abstract : Among human immunodeficiency virus individuals with syphilis, mild or greater severity photophobia, vision loss, gait incoordination, and moderate or greater severity hearing loss were more common in those with a reactive cerebrospinal fluid Venereal Disease Research Laboratory test. Abstract: Background: Current guidelines recommend lumbar puncture (LP) in patients with syphilis who have neurologic symptoms. Methods: A total of 81 human immunodeficiency virus (HIV)-uninfected individuals and 385 HIV-infected individuals enrolled in a study of cerebrospinal fluid (CSF) abnormalities in syphilis underwent LP and a structured symptom history, including assessment of headache; stiff neck; photophobia; ocular inflammation; vision, hearing, or sensory loss; or gait incoordination. Neurosyphilis was defined as a reactive CSF-Venereal Disease Research Laboratory (VDRL) test. Association between categorical variables was assessed using χ 2, Fisher exact test, or logistic regression. Association between continuous and categorical variables was assessed using Mann-Whitney U test. Results: CSF-VDRL was reactive in 20 (24.7%) HIV-uninfected and 68 (17.7%) HIV-infected ( P = .14) individuals. No symptom was more common in HIV-uninfected individuals with neurosyphilis. Among the HIV-infected, the odds of a reactive CSF-VDRL were higher in those with mild or greater severity photophobia (2.0 [95% confidence interval [CI], 1.1–3.8]; P = .03), vision loss (2.3 [1.3–4.1]; P = .003), or gait incoordination (2.4 [1.3–4.4]; P = .006); or moderate or greater severity hearing loss (3.1 [1.3–7.5]; P = .01). Diagnostic specificity of these 4 symptoms for neurosyphilis was high when limited to moderate or greater severity (91.6%–100%); however, the diagnostic sensitivity was low (1.5%–38.1%). Conclusions: Among HIV-infected patients with syphilis, 4 specific neurologic symptoms are more common in those with a reactive CSF-VDRL. Lack of symptoms does not guarantee that the CSF-VDRL is nonreactive, regardless of HIV status.